Pengaruh Tatanan Massa terhadap Kenyamanan Termal Jalur Pedestrian Jalan Mangkubumi Yogyakarta - Febriarto, Prasetyo; Fidali, Nurizka (Mintakat: Jurnal Arsitektur, 2024)
The effect of a humid tropical climate affects urban activities which results in the emergence of heat islands that occur in microclimate areas, especially in urban areas which are synonymous with building density, concrete forests, lots of hard elements such as pavements which cause city temperatures to heat up. This phenomenon also has an impact on the activities that occur in one of the areas that are the research locations in outer space on the Prince Mangkubumi Yogyakarta road with a special location on the pedestrian path. choose the pedestrian path because this path has an environment in the form of open space that is often passed by pedestrians, used for social interaction, a path that has become a tourist destination. This line is also equipped with enclosures in the form of buildings with various heights and functions that coincide with the buildings next to it. The path on this road has vegetation that does not provide enough shade for the pedestrian path along Jalan Pangeran Mangkubumi. Seeing this urgency, thermal comfort testing must be carried out focused on pedestrian paths. The aim of this research is to measure the level of thermal comfort and identify its factors. The research was conducted using the Envi - Met 3.1 software simulation method and then analyzed based on outdoor thermal theories, Urban Heat Island and related articles. The stages of this research were in the form of research preparation in the form of an initial survey, the research stage in the form of data collection (primary and secondary), the analysis stage in the form of modeling simulation using Envi-Met software, and the expected findings emerged. This research tries to provide an overview of the thermal distribution from environmental simulation results and then analyzed. Thermal distribution using the existing condition model, namely the outdoor environment of the pedestrian path on Jalan Pangeran Mangkubumi.